2010
DOI: 10.1039/b924742d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of axial pyridine coordination on a saddle-distorted porphyrin macrocycle: stabilization of hexa-coordinated high-spin Fe(iii) and air-stable low-spin iron(ii) porphyrinates

Abstract: We have reported here the effect of axial ligand L (L: pyridine/substituted pyridine) on Fe(III)(tn-OEP)Cl/Fe(III)(tn-OEP)ClO(4) that first form high-spin Fe(III)(tn-OEP)(L)(2).X (X: Cl, ClO(4)) which, on longer exposure, spontaneously auto reduce to a series of air stable Fe(II)(tn-OEP)(L)(2) complexes. The introduction of four nitro groups into the meso-positions of octaethyl porphyrin (tn-OEP), severely distorts the porphyrin macrocycle which enables the facile isolation of a rare family of high-spin Fe(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 68 publications
3
24
0
Order By: Relevance
“…or strong Lewis acidity of iron(III) porphyrins causes the reduction to iron(II) porphyrins in presence of an axial ligand such as pyridine, imidazoles. Patra et al 24. also reported high‐spin [Fe III (tn‐OEP)(L) 2 .X] (X: Cl, ClO 4 ) porphyrins spontaneously autoreduced to low‐spin [Fe II (tn‐OEP)(L) 2 ] complexes depending upon axially bounded strong field ligand L (L: pyridine/substituted pyridine).…”
Section: Resultsmentioning
confidence: 98%
“…or strong Lewis acidity of iron(III) porphyrins causes the reduction to iron(II) porphyrins in presence of an axial ligand such as pyridine, imidazoles. Patra et al 24. also reported high‐spin [Fe III (tn‐OEP)(L) 2 .X] (X: Cl, ClO 4 ) porphyrins spontaneously autoreduced to low‐spin [Fe II (tn‐OEP)(L) 2 ] complexes depending upon axially bounded strong field ligand L (L: pyridine/substituted pyridine).…”
Section: Resultsmentioning
confidence: 98%
“…We note, however, that this sizable degree of the asymmetry contradicts the experimental observation, whereas the order of the magnitude for the D-value and its sign seems reasonable, considering the accuracy of the theoretical method for the 3d 5 electron configuration of ferric iron cases. 11,51 As described above in (a) for the case of the Mn(II) porphyrins, the theory still overestimates the degree of the asymmetry. Importantly, the theoretical D-value of complex 3 + , +3.1241 cm -1 can be compared with the experimental one, which falls in the range of order of cm -1 to 10 cm -1 , as determined by the magnetic susceptibility analysis revisited in this work (see below and Fig.…”
Section: Resultsmentioning
confidence: 87%
“…18,52 Recently, hexa-coordinated (pseudo-octahedral) high spin cobalt(II) complexes with sizable ZFS parameters comparable to the microwave excitation energy of X-band ESR (9.5 GHz or 0.3 cm -1 ) have been studied. 18,28,[51][52][53][54][55][56][57][58][59][60][61][62][63][64] Palii and co-workers synthesized NH4[Co II (hfac)3] and investigated the electronic structures and magnetic characters as SMM by using of ESR spectroscopy and AC/DC magnetic susceptibility measurements. 51 From the theoretical viewpoint, the principal values of the magnetic tensors such as the g-, ZFS D-and hyperfine A-tensors for the 3d 7 electron configuration of high spin metal ions are still the focus of the current quantum chemical calculations.…”
Section: (C) Cis-[co(hfac)2(h2o)2] (4 S = 3/2)mentioning
confidence: 99%
“…Heme functions are highly sensitive to changes in the macrocycle because of its high flexibility , . Some earlier studies showed that the porphyrin core could regulate the spin state of nickel(II) ions and the electronic ground states of low‐spin (LS) iron(III) ions, , in a porphyrin on the basis of the expansion or contraction of the core. We found that the size‐matching rule could be used to obtain a combination of variable core and alterable iron species.…”
Section: Resultsmentioning
confidence: 99%